The Implementation Level of Clean and Healthy Living Behavior Among University Students: An Analytical Study - Lia Junita Harahap; Lena Juliana Harahap (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Clean and Healthy Living Behavior (CHLB) is one of the key promotive and preventive approaches to improving public health. As a productive age group, university students play a significant role in fostering a healthy lifestyle culture both on campus and within the wider community. This study aimed to analyze the level of CHLB implementation among university students. A descriptive quantitative research design with a survey method was employed. The research instrument consisted of a CHLB questionnaire covering indicators of personal hygiene, nutritious food consumption, physical activity, rest patterns, environmental hygiene, utilization of health services, and smoke-free behavior. The data were analyzed using descriptive statistics, including percentages and mean scores. The findings revealed that the overall level of CHLB implementation among university students was categorized as high. Personal hygiene and environmental hygiene achieved the highest scores, whereas physical activity and rest patterns were only categorized as moderate. These findings indicate the need for sustainable health promotion programs to enhance students' awareness and encourage the consistent adoption of clean and healthy living behaviors.